Reduced fibrosis in recurrent HCV with tacrolimus, azathioprine and steroids versus tacrolimus: randomised trial long term outcomes. Issue 6 (16th October 2013) - Manousou, Pinelopi; Cholongitas, Evangelos; Samonakis, Dimitrios; Tsochatzis, Emmanuel; Corbani, Alice; Dhillon, A P; Davidson, Janice; Rodríguez-Perálvarez, Manuel; Patch, D; O'Beirne, J; Thorburn, D; Luong, TuVinh; et al.
Abstract : Objective: Early results of a randomised trial showed reduced fibrosis due to recurrent HCV hepatitis with tacrolimus triple therapy (TT) versus monotherapy (MT) following transplantation for HCV cirrhosis. We evaluated the clinical outcomes after a median 8 years of follow-up, including differences in fibrosis assessed by collagen proportionate area (CPA). Design: 103 consecutive liver transplant recipients with HCV cirrhosis receiving cadaveric grafts were randomised to tacrolimus MT (n=54) or TT (n=49) with daily tacrolimus (0.1 mg/kg divided dose), azathioprine (1 mg/kg) and prednisolone (20 mg), the last tailing off to zero by 6 months. Both groups had serial transjugular biopsies with hepatic venous pressure gradient (HVPG) measurement. Time to reach Ishak stage 4 was the predetermined endpoint. CPA was measured in all biopsies. Factors associated with HCV recurrence were evaluated. Clinical decompensation was the first occurrence of ascites/hydrothorax, variceal bleeding or encephalopathy. Results: No significant preoperative, peri-operative or postoperative differences between groups were found. During 96 months median follow-up, stage 4 fibrosis was reached in 19 MT/11 TT with slower fibrosis progression in TT (p=0.009). CPA at last biopsy was 12% in MT and 8% in TT patients (p=0.004). 14 MT/ three TT patients reached HVPG≥10 mm Hg (p=0.002); 10 MT/three TT patients, decompensated. Multivariately, allocated MT (p=0.047, OR 3.23, 95% CI 1.01 to 10.3) was independently associated with decompensation: 14 MT/ seven TT died, and five MT/ four TT were retransplanted. Conclusions: Long term immunosuppression with tacrolimus, azathioprine and short term prednisolone in HCV cirrhosis recipients resulted in slower progression to severe fibrosis assessed by Ishak stage and CPA, less portal hypertension and decompensation, compared with tacrolimus alone. ISRCTN94834276: —Randomised study for immunosuppression regimen in liver transplantation.